Gabriela Mistral’s (Im)possible Return to Chile from a Neurosciences Perspective - Martina Bortignon (Literatura: Teoría, Historia, Crítica)
This article analyzes the ambiguity of an imaginary homecoming in Poema de Chile and Lagar by Gabriela Mistral, written while the Chilean poet was living abroad. In these works, her longing for Chile materializes through highly detailed perceptual scenes. Hinged on a neuroscience perspective, the analysis applies a vision of memory as a creative rather than reproductive process, the category of imagery and fMRI observation of neural networks in memory and poetry creation. The hypothesis states that the creation of a poem, for Mistral and under certain circumstances, would translate into the activation of a multiperceptual mental imagery that allows her to travel through time and space to relive atmospheres, situations, and natural elements of her longed-for homeland. However, in Mistral’s case this imaginary journey is quite ambivalent, since it carries the intuition of its own impossibility and converges in the subject’s drive to disintegrate within the sensory elements remembered in the poems.